Pelatihan Pemanfaatan Akun Tiktok dalam Pembelajaran Bahasa Indonesia pada Remaja di Lingkungan RW 03 Kelurahan Meruyung Limo Depok - Atmapratiwi, Heppy; Wiyanti, Endang; Sudrajat, Yayan (Presisi Jurnal Pengabdian Masyarakat, 2024)
The aim of this community service is to socialize the use of TikTok social media in teenagers' Indonesian language learning. Through initial observations and interviews with the people of RW 03 Meruyung, Limo, Depok, it was revealed that local teenagers do not fully understand many things and Indonesian language materials. Even though the teenager is a junior high school student who also has to learn Indonesian at school. Therefore, this community service activity aims to ensure that teenagers in the RW 03 Meruyung, Limo, Depok area can understand Indonesian through the media that is currently most frequently used. In this way, it is hoped that teenagers will be more enthusiastic and quickly understand Indonesian language material through content that is more contemporary and not boring. The results of this service activity include preparing materials or studies to help teenagers understand and utilize Tiktok social media in learning Indonesian. Apart from that, the team will create a published article to convey the achievements of this community service activity to the wider community, with the hope that the information disseminated can provide meaningful benefits. Thus, it is hoped that this effort can make an effective contribution in overcoming social problems, especially educational gaps in society.